Does the number of taxpayers matter for optimum collection of Turnover tax category -B-taxpayers - Baharu Sisay Negatu; Nidhi Walia (Multidisciplinary Business Review)
Taxation is a fundamental tool of government fiscal policy. This study investigates the factors influencing Turnover Tax collection among category - B - taxpayers in Ethiopia, focusing on the relationships between taxpayer registration, knowledge, attitude, and tax collection. An exploratory research design using a mixed-methods approach was employed. From 797 registered taxpayers in the zone, 266 were selected through simple random sampling. Additionally, 36 employees from 18 Woreda offices were chosen purposively, and 19 managers were interviewed, yielding a total sample size of 321. Data was collected from both primary sources (questionnaires and interviews) and secondary sources (published and unpublished materials) and analysed using descriptive and inferential statistics. Findings indicate that taxpayer knowledge, payment convenience, taxpayer attitudes, and enforcement through penalties significantly affect tax collection. A strong negative correlation was found between tax collection and both taxpayer registration gaps and corruption. The study recommends government action on ICT infrastructure, taxpayer education, and anti-corruption measures. These findings offer practical insights for Ethiopian tax policymakers to identify weaknesses in registration and collection processes, improve compliance, and design more effective tax strategies. However, the study’s generalizability is limited by its focus on the South Gonder Zone, the sample size, and the chosen research design.